2008
DOI: 10.1121/1.2931953
|View full text |Cite
|
Sign up to set email alerts
|

Influence of in situ, sound-level calibration on distortion-product otoacoustic emission variability

Abstract: Standing waves can cause errors during in-the-ear calibration of sound pressure level (SPL), affecting both stimulus magnitude and distortion-product otoacoustic emission (DPOAE) level. Sound intensity level (SIL) and forward pressure level (FPL) are two measurements theoretically unaffected by standing waves. SPL, SIL and FPL in-situ calibrations were compared by determining sensitivity of DPOAE level to probe-insertion depth (deep, “shallow”) for a range of stimulus frequencies (1−8 kHz) and levels (20−60 dB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
141
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 114 publications
(146 citation statements)
references
References 39 publications
(53 reference statements)
2
141
0
Order By: Relevance
“…This reference was then used to set the level of stimuli during all DPOAE measurements. We recognize that SPL calibrations in closed ear canals are sometimes characterized by errors introduced as a result of standing waves (e.g., Siegel, 1994Siegel, , 2002Siegel and Hirohata, 1994;Scheperle et al, 2008). In this study, however, SPL calibrations were chosen in order to use conditions identical to those used in our previous study, the data from which are being combined with the present data.…”
Section: Methodsmentioning
confidence: 94%
“…This reference was then used to set the level of stimuli during all DPOAE measurements. We recognize that SPL calibrations in closed ear canals are sometimes characterized by errors introduced as a result of standing waves (e.g., Siegel, 1994Siegel, , 2002Siegel and Hirohata, 1994;Scheperle et al, 2008). In this study, however, SPL calibrations were chosen in order to use conditions identical to those used in our previous study, the data from which are being combined with the present data.…”
Section: Methodsmentioning
confidence: 94%
“…The source calibration used in the present study and the earlier study by Scheperle et al ͑2008͒ can be expected to accurately decompose incident and reflected pressure waves in the ear canal. FPL and IPL are derived sound-level measures resulting from the source calibration and, more specifically, the Thevenin-equivalent source characteristics ͑imped-ance and pressure͒.…”
Section: Discussionmentioning
confidence: 99%
“…Neely and Gorga (1998) compared behavioral threshold measurements between 0.5 and 8 kHz based on pressure and acoustic intensity calibration and concluded that intensity calibration in the ear was preferable above 2 kHz. Scheperle et al (2008) reported that an in-theear stimulus calibration based on forward pressure level or intensity level provided more consistent DPOAE measurements between 2 and 8 kHz compared to a calibration based on total pressure. Based on analyses of measurements between 0.25 and 6 kHz, Withnell et al (2009) proposed that either forward pressure or the fraction of total pressure at the tympanic membrane that is not reflected at the tympanic membrane be used to specify behavioral hearing threshold rather than total pressure.…”
Section: Constant Stimulus-level Proceduresmentioning
confidence: 99%